Pengaruh Fomo (Fear of Missing Out), Positive Emotion, Dan Shopping Lifestyle Terhadap Impulse Buying di Tiktok Shop (Survei Pada Mahasiswa di Surakarta) - Ervina Kumalasari; Rizky Ramadhan Aprian Aditama (Teewan Journal Solutions, 2026)
This study aims to analyse the significant impact of Fear of Missing Out (FOMO), Positive Emotion, and Shopping Lifestyle on Impulse Buying behaviour on the TikTok Shop platform. Using a quantitative approach with primary and secondary data sources, this study collected data through questionnaires, observations, and literature studies. The research sample consisted of 130 students in Surakarta who were selected using convenience quota sampling techniques. The data analysis methodology used was comprehensive, covering instrument testing (validity and reliability), classical assumption testing (multicollinearity, autocorrelation, heteroscedasticity, and normality), and multiple linear regression analysis supplemented with hypothesis testing (t-test and F-test) and the coefficient of determination (R2). The results showed that all instruments were valid (p < 0.05) and reliable (Cronbach's Alpha > 0.60), and the regression model met all the classical assumptions tested. The regression model formed was Y = 1.632 + 0.354 X₁ + 0.200 X₂ + 0.234 X₃. Partially (t-test), the variables FOMO (X₁), Positive Emotion (X₂), and Shopping Lifestyle (X₃) were proven to have a statistically significant effect on Impulse Buying (Y). The F-test results also confirmed that this regression model was feasible and significant (fit). Furthermore, the coefficient of determination (Adjusted R²) value of 0.584 indicates that 58.4% of the variation in Impulse Buying can be explained simultaneously by the three independent variables, while the remaining 41.6% is influenced by other factors outside the scope of this study.